Assessing the spatial distribution and sources of heavy metal pollution in the snow cover: A case study from Pavlodar, Northeastern Kazakhstan - Alina Faurat; Dinara Yessimova; Gulmira Satybaldiyeva; Askhat Kuatbayev; Aizhan Utarbayeva; Ainagul Kaliyeva; Kairat Akhmetov; Shujaul Mulk Khan; Zeeshan Ahmad; Seilkhan Rakhmanov (PLoS ONE, 2025)
This study assesses heavy metal contamination in the snow cover of northeastern Kazakhstan by analyzing both the melted filtrated water and the solid sediment after filtration near various pollution sources. The research examines the impact of oil refining, thermal power plants (northern industrial zone), aluminum production (eastern industrial zone), and transportation on heavy metal dispersion. Results indicate that Zn, Cr, and Pb concentrations in the solid phase of snow in residential areas exceed those in industrial zones, reaching 436.6, 259.1, and 218.6 mg/kg, respectively. The highest overall concentrations were found for barium (949.4 mg/kg) and manganese (638.1 mg/kg). In the liquid fraction (meltwater), Zn (58.6 μg/l) and Sr (34.8 μg/l) were predominant, while Mn (28.3 μg/l) was the main pollutant in the eastern industrial zone. Dust load values in the snow cover ranged from 42.3 to 418.5 mg/m²/day, with the highest pollution load observed for Cd, Pb, and Mo. Despite variations in dust load across the city (135.5 mg/m²/day in the northern industrial zone, 152.3 mg/m²/day in the eastern industrial zone, and 147.1 mg/m²/day in residential areas), the overall dust pollution level remains low. However, a sanitary-hygienic assessment revealed that most heavy metal concentrations in snow exceed maximum permissible levels for soil in areas influenced by industrial facilities and transportation, except for Mo, V, and Mn. The ecological risk index of snow pollution in Pavlodar was calculated at 192.13, indicating a high potential ecological risk. These findings highlight the importance of snow as an indicator of environmental pollution and the need for continuous monitoring to assess urban contamination trends.